2007
DOI: 10.1530/eje-07-0445
|View full text |Cite
|
Sign up to set email alerts
|

Long-term neurodevelopmental outcome in conservatively treated congenital hyperinsulinism

Abstract: Background: Congenital hyperinsulinism (CH) is treated surgically in many centers (near

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 24 publications
3
41
0
2
Order By: Relevance
“…Earlier recommendations of prompt subtotal pancreatectomy to reduce the risk of brain damage from hypoglycaemia are no longer supported for a number of reasons: i) focus ablation is sufficient to cure patients with focal disease (8), ii) some patients with diffuse CHI may be treated successfully by medication and eventually undergo clinical remission after months or even several years (40)(41)(42) and iii) subtotal pancreatectomy is complicated by an increased risk of subsequent diabetes and mild malabsorption (43). The switch towards a more conservative approach in diffuse CHI (if possible) and a rapid focal resection in focal CHI in many centres implies that a uniform definition of CHI as mild/ moderate or severe according to treatment modality may be questioned.…”
Section: Prevalencementioning
confidence: 99%
“…Earlier recommendations of prompt subtotal pancreatectomy to reduce the risk of brain damage from hypoglycaemia are no longer supported for a number of reasons: i) focus ablation is sufficient to cure patients with focal disease (8), ii) some patients with diffuse CHI may be treated successfully by medication and eventually undergo clinical remission after months or even several years (40)(41)(42) and iii) subtotal pancreatectomy is complicated by an increased risk of subsequent diabetes and mild malabsorption (43). The switch towards a more conservative approach in diffuse CHI (if possible) and a rapid focal resection in focal CHI in many centres implies that a uniform definition of CHI as mild/ moderate or severe according to treatment modality may be questioned.…”
Section: Prevalencementioning
confidence: 99%
“…In case of diffuse HI, where all b-cells are involved throughout the pancreas, long-term and intensive medical treatment is the only alternative to the near-total pancreatectomy, which leads to recurrent post-operative hypoglycemias in 60% of patients and then insulin-dependent diabetes within a few years in all patients (7,8). Thus, the challenge for diazoxide-unresponsive diffuse HI is to find an efficient and well-tolerated long-term medical treatment, especially as progressive b-cells apoptosis may be responsible for spontaneous remission (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Steinkrauss et al [20] reported 68 patients with CH; one third had developmental delay which was more prevalent in surgical group. Mazor et al [21] studied 21 Ashkenazi children 12 with diffuse and 9 with focal disease; all of them received medical treatment. Most of the developmental problems resolved by school age and all children were enrolled in regular education.…”
Section: Discussionmentioning
confidence: 99%